2023
DOI: 10.17531/ein/163289
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Composite Tire Numerical Simulation Based on the Frequency Response Analysis

Abstract: Reliability and maintenance analysis in transport focus on the main objective of accident and incident investigations that benefit to better understanding of the causes of accidents and prevention of them in the future. The conducted research presents theoretical and experimental research on composite pneumatic tire used in transport engineering. The approach of the numerical simulation sequence which is offered in this research facilitates engineers in efficient determination of the dynamic properties and beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Various methods could be used for the verification of the results obtained from conformal mapping and finite element techniques. A frequency response analysis [33] could be one of the options, physical modeling could be the second one, and analogue experimental techniques could be the third one. The first one requires a large set of data and the second one is very expensive.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…Various methods could be used for the verification of the results obtained from conformal mapping and finite element techniques. A frequency response analysis [33] could be one of the options, physical modeling could be the second one, and analogue experimental techniques could be the third one. The first one requires a large set of data and the second one is very expensive.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…Vibrations, among others, influence fatigue, which is a critical design issue in wind energy structures. An example of methods for analyzing such vibrations, based on frequency response analysis, is studied in [2,3]. Specifically, the analysis showed that porous structure fractions can improve the adaptive characteristics of passive control systems utilized for vibrationreducing applications in the low and intermediate frequency ranges for unmanned aerial vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation and interaction of electromagnetic waves in a substance are influenced by factors such as the substance's properties and water content. Mykola Karpenko and collaborators [14] utilized piezoelectric micro-vibration testing and frequency analysis to evaluate the properties of tire materials. Their results demonstrated the applicability of the frequency response optimization method in the numerical simulation of composite tires.…”
Section: Introductionmentioning
confidence: 99%